Fluorine and nitrogen co-doped mesoporous carbon derived from polytetrafluoroethylene@melamine sponge for supercapacitor application. (June 2021) - Jia, Haiyang; Zhu, Jingfang; Zhang, Meng; Sang, Shijing; Hu, Feng; Zhang, Fen
Highlights: PTFE@melamine sponge is constructed to synthesized F, N co-doped porous carbon. The doping amount of F and N is 1.2 and 2.7 at.%, respectively. The co-doped carbon delivers a specific capacitance of 299 F g −1 at 1 a g −1 . The supercapacitor harvests a specific energy of 8.3 W h kg −1 in 6 M KOH. Abstract: By using polytetrafluoroethylene@melamine sponge composite as the precursor, a nitrogen and fluorine co-doped porous carbon is prepared via a chemical etching process. The specific surface area and total volume of the mesoporous carbon are 1799 m 2 g −1 and 1.48 m 3 g −1, respectively. The doping amount of the fluoride and nitrogen in the resulting co-doped carbon is determined to be 1.2 at.% and 2.7 at.%, respectively. In a three-electrode system in 6 M KOH electrolyte, when mass loading of active material is 4 and 6 mg, electrodes deliver specific capacitances of 299 and 284 F g −1 at a current density of 1 A g −1, respectively. In a symmetric-electrode system in the same electrolyte, an electrode shows the specific capacitance of 233 F g −1 at the same current density. In aqueous electrolyte, the assembled simulated supercapacitor reaps a maximum specific energy of 8.3 W h kg −1 at a specific power of 101 W kg −1 . Under the current density of 5 A g −1, after 6000 cycles, the 94.1% remaining capacitance indicates a good cycle stability. Findings demonstrate the synthesized fluorine and nitrogen co-doped porous carbon can be used as electroactive material for high-performance supercapacitor.